Expression of RXLR effectors in the EC-1 clonal lineage of Phytophthora infestans in Peru - Izarra, Myriam (2016)
Potato (Solanum tuberosum L.) is nowadays one of the most important food crops. It is prone to the disease known Late blight caused by the oomycete pathogen Phytophthora infestans, which secrete a hundreds of effectors that act as virulence factors. Little is known of the diversity of virulence genes of the strains that belong to a clonally reproducing lineage EC-1. In this paper, through the transcriptome sequencing of potato and P. infestans interaction, we identified differentially expressed RXLR type effector genes in two P. infestans isolates EC-1, being confirmed by qRT-PCR. The isolates, originate from cultivated potato in the central Peruvian Andes, have different virulence patterns. Effector genes, were silenced in one isolate, such as Avr-vnt1 in POX 109 and for Avh9.1 homolog in POX 067, but expressed in the other. The transcriptomics results were compared with three additional isolates from the EC-1 lineage. The information on the pathogen effector repertoire and its expression should be informative for resistance breeding. Discovery of silenced effectors in the pathogen populations can guide the use of specific R genes in the breeding programs. For example in the Andean setting where EC-1 lineage dominates the Rpi-vnt1 would not be recommended.